Angiotensin I-converting enzyme (ACE) inhibitory activities of enzymatically hydrolyzed jackfruit seed protein - Niemrungruang, Samuchaya; Wattansirittham, Ladda Sanduean; Saengprakai, Jenpen (Agriculture and Natural Resources, 2026)
Importance of the work: Angiotensin-converting enzyme (ACE) has been well-recognized for its role in blood pressure regulation. Jackfruit seed protein hydrolysates (JSPs) are produced via enzymes. Objectives: To assess the potential of jackfruit seed proteins as a functional food for high blood pressure treatment based on bioactive peptides. Materials and Methods: The ACE inhibitory activities were investigated of the JSPs produced via pepsin, trypsin and chymotrypsin enzymes. After hydrolysis, smaller JSP molecules (≤ 3 kDa) were collected following ultrafiltration and further purified using solid phase extraction (SPE). The ACE inhibitory activity analysis of all peptides revealed positive results. Hence, the peptides were further separated into fractions using hydrophilic interaction liquid chromatography (HILIC) and reversed phase-high performance liquid chromatography (RP-HPLC) and subsequently, analysis of the inhibitory properties of JSP fractions against ACE was carried out. Results: The mean (± SD) yield of protein from jackfruit seeds extracted using sonication at 30% amplitude was 18.52 ± 0.6% dry basis. The JSPs had a mean (± SD) ACE-inhibitory activity of 77.75 ± 0.17% and a half maximal inhibitory concentration (IC50) of 0.54 mg/mL. The impediment to ACE activity by the HILIC 90%_JSP_ACN+0.1%FA fraction was the highest. Based on further RP-HPLC fractionation of this HILIC fraction, the inhibition efficiency of fraction 6 (HILIC90%_JSP_RP-HPLC_6) against ACE was exemplary. Main finding: JSPs are promising alternative sources of antihypertensive functional food, food ingredients and nutraceuticals.